The factors contribute towards customer satisfaction at Bank Simpanan Nasional (BSN) Merbok / Nur Syuhada Muhamad Sabri and Nur Wahida Abdul Talib - Muhamad Sabri, Nur Syuhada; Abdul Talib, Nur Wahida (2018)
This chapter focused on the background of the study which is the factors contribute towards customer satisfaction at Bank Simpanan Nasional (BSN) Merbok. The presentation of this chapter begins with the research background, followed by the problem statement, research questions, research objectives, scope of the study, significant of the study and lastly the definition of terms and concepts used in this study.